Significant Structural Alterations and Functional Connectivity Alterations of Cerebellar Gray Matter in Patients With Somatic Symptom Disorder - Liang, Huai-Bin; Dong, Liao; Cui, Yangyang; Wu, Jing; Tang, Wei; Du, Xiaoxia; Liu, Jian-Ren (Frontiers in Neuroscience, 2022)
Objective: Recent studies have revealed a strong association between the cerebellum and psychiatric disorders. However, the structural changes in the cerebellar regions and functional connectivity (FC) patterns in patients with somatic symptom disorder (SSD) have not been elucidated. Methods: Thirty-seven patients with SSD (29 drug-naïve and 8 medicated patients) and 37 sex- and age-matched healthy controls (HC) were recruited and underwent resting-state fMRI scans. The SUIT cerebellar atlas-based voxel-based morphometry (VBM) was employed to investigate the changes in cerebellar regional gray matter (GM). Seed-based FC was further computed to explore the pattern of abnormal FC across the whole brain. Correlations were calculated to investigate the relationship between cerebellar structural (and FC) changes and clinical characteristics. Results: After controlling for age, sex, TIV, medication, and mead FD covariates, all patients with SSD had increased mean GM volume in the posterior lobules of the cerebellum bilaterally when compared with HC, specifically, in the bilateral cerebellar Crus I and Crus II. Patients with SSD showed significantly stronger FC between the right Crus I & II and bilateral precuneus inferior parietal region, and postcentral gyrus, extending to the superior parietal lobe, cingulate gyrus and the white matter sub-gyral. In addition to the two clusters, right lingual gyrus was also a surviving cluster with significantly higher FC. Partial correlation analysis revealed that the degree of regional GMV increase in the two significant clusters and the HAMD score was negatively correlated. Moreover, the FC of right Crus I & II with the left parietal lobe and right lingual gyrus were also negatively associated with the HAMD score. Conclusions: SSD exhibited significant microstructural changes and changes in FC pattern in the posterior cerebellar lobe. These results shed new light on the psychological and neural substrates of SSD and may serve as a potential treatment target for SSD based on the cerebellar area.